Validity and reliability of the Perceived Efficacy and Goal Setting System (PEGS) for Brazilian children/Validade e confiabilidade do Perceived Efficacy and Goal Setting System (PEGS) para crianças brasileiras - Costa, Samara de Araújo; Bigonha Ruggio, Carina Iracema; Missiuna, Cheryl; Araújo, Clarice Ribeiro Soares; Magalhães, Lívia de Castro (Cadernos Brasileiros de Terapia Ocupacional, 2018)
Introduction: The engagement in client-centered practice requires instrumentation that allows the participation of the child and family in the definition of treatment goals. Objective: The aim of the present study was to pilot a translated version of the Perceived Efficacy and Goal Setting System (PEGS) and determine its validity and reliability for clinical use with Brazilian children. Method: Eighty children six to nine years old (40 public school children and 40 private school children), as well as their caregivers and teachers, completed the PEGS. Results: The children understood the pictures and interview procedures. Caregivers and teachers reported no difficulties in understanding the questionnaires. Gender, age, and type of school had no significant influence over the children’s scores. Cultural influence on the response to two items was identified but could be resolved with extra explanation. Stability of the goals was supported and the children, caregivers, and teachers appear to share views regarding the overall abilities of the children. Conclusion: The PEGS has potential for clinical use with Brazilian children, but clinicians should be aware that some items require further instructions. The usefulness of the PEGS as a tool to promote client-centered practice among Brazilian occupational therapists should be investigated.